HUBUNGAN PATRON – KLIEN ANTARA GERMO DAN PSK (Studi Kasus Perumahan Jondul Lama Kelurahan Rejosari Kecamatan Tenayan Raya Pekanbaru) - Wita Jaya; Basri, " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Research conducted from June to August 2013, in the Village Housing Jondul Lama Rejosari District of Tenayan Kingdom Pekanbaru aims to determine how the client Patron history between pimps with prostitutes in the Old Village Housing Jondul Rejosari District of Tenayan Kingdom, the relationship between the prostitute and pimp how roles reciprocal basis between the procurer (patron) with PSK (client) in the Old Village Housing Jondul Rejosari District of Tenayan Kingdom. The method used is a qualitative method (Descriptive Research). Informants used is seven prostitutes and two pimps were there in the Old Jondul Housing and community leaders. Data was collected through in-depth interviews ( indepth interviews ) and observations , then the data that has been obtained qualitatively analyzed .The results showed that the Client Patron relationship between pimps and prostitutes is motivated by the need to make life as a pimp and prostitute patron needs workers also need work. The relationship between them begins with a relationship without a written agreement, but based on mutual trust of each party. As a patron, the pimp has a function as an intermediary or dealer to the customer , arrange the working systems and as head of the family , accompanied by PSK function as a facilitator in the business world of prostitution. The relationship anatara pimps and prostitutes in the Jondul Lama urban residential districts Rejosari Tenayan Kingdom is progressing well and the positive lead to the kinship between the two. Pimps have a role to PSK ( client ) both at work and in daily life to direct, control, and protect prostitutes. Likewise with sex workers who have worked in accordance with the role that pimps command, perform its obligations as workers, serve and delight customers. So the relationship that exists in the world of covert peostitusi between pimps and prostitutes who were in the Village Housing Jondul Lama Rejosari Tenayan District of Pekanbaru 's Kingdom can be said are good and positive.Keywords : Patron - Client, Panti Massage Plus, PSK.